Neuroticism, stress, and coping in the context of an anagram-solving task - Boyes, M; French, D (Elsevier, 2010)
Research examining the relationship between neuroticism and coping has been limited by reliance on dispositional coping measures and/or retrospective reporting with long time-lags. The current experiment evaluated an anagram-solving task as a laboratory-stressor with which to examine neuroticism-related differences in situational coping. One hundred and twenty-four participants (with neuroticism scores in the top or bottom quartiles) were assigned to one of two conditions across which anagram difficulty and level of controllability were manipulated. Individuals in the high-stress condition solved fewer anagrams, appraised the task more negatively, reported lower mood and self-esteem, and engaged in more emotion-focused and less task-focused coping than individuals in the mild-stress condition. High- neuroticism participants engaged in more emotion-focused and avoidance coping than low-neuroticism participants regardless of which condition they were assigned to. In the mild-stress condition, high-neuroticism participants engaged in less task-focused coping than low-neuroticism participants. No neuroticism-related differences in task-focused coping was obtained in the high-stress condition. It is concluded that (1) the anagram-solving task is a promising laboratory-stressor with which to examine individual differences in appraisal and coping, and (2) neuroticism is associated with task-focused, emotion-focused, and avoidance coping in the context of this task, which overcomes limitations of previous research in this area.